The application of computational fluid dynamics for technique prescription in underwater kicking - Lyttle, A.; Keys, M. (Biomechanics and Medicine in Swimming X, 2006)
Computational Fluid Dynamics (CFD) was developed to provide answers into problems which have been unobtainable using physical testing techniques. This study sought to discriminate between the active drag and propulsion generated in underwater dolphin kicking. A 3D Image of an elite swimmer was animated using results from a kinematic analysis of the swimmer performing large/slow and small/fast dolphin kicks underwater. The CFD model was developed around this input data. Changes were also made to the input kinematics (ankle plantar flexion angle) to demonstrate the practical applicability of the CFD model. The results demonstrated an advantage in using the large, slow kick over the small, fast kick over the velocity range that underwater dolphin kicks are used. This highlights the potential benefits of using CFD models in technique prescription.